Skrining Fitokimia dan Uji Aktivitas Antibakteri Madu Putih Sumbawa terhadap Bacillus megaterium - Nurmi Hasbi; Rosyunita Rosyunita; Adelia Riezka Rahim; Eusthacius Hagni Wardoyo; Ida Ayu Arnawati; Saskia Safarina Haza; Lale Nandhita Hulfifa; Abiel Dwi Cahya Firdaus Alamsyah; I Komang Satya Validika (Jurnal Penelitian Pendidikan IPA, 2023)
Bacillus megaterium is a bacteria that causes human infections, causing keratitis, skin infections, brain abscesses and tissue infections. Treatment often uses chemical antibiotics. However, long-term antibiotics can cause new health problems such as resistance. Therefore, antibacterial ingredients are needed that can not only inhibit the growth of bacteria but also do not have a negative impact on health such as honey. Honey is thick, it can cure various diseases such as gastrointestinal, stomach, skin diseases, acute respiratory infections and coughs. This research aims to determine the ability of Sumbawa white honey as an antibacterial against B. megaterium. The method used in this research is paper disc diffusion. There were five treatments used in this study, between 100%, 75% and 25% honey concentrations, DMSO negative control and chloramphenicol positive control with five replications each. The results of the antibacterial activity test showed that the 100% concentration had an inhibitory zone diameter of 2.59 mm, then the 75% concentration was 1.46 while the 25% concentration was 0 mm. When compared with positive control, white honey was lower antibacterial. If it is in the white honey category, the inhibition zone category is included in the lower category.